Biometria testicular, parâmetros seminais e proteoma do plasma seminal de carneiros Morada Nova, variedade branca, submetidos à insulação escrotal - Rocha, David Ramos da (2013)
The present study was conducted to evaluate the effects of heat stress on testis and semen criteria, and seminal plasma proteome of rams. Scrotal insulation (SI) was in place for eight days, using six rams. Animals were evaluated before (day 0), during and after SI until semen parameters returned to normal. Scrotal circumference, other testis parameters and sperm motility decreased after SI but returned to pre-insulation values on days 71, 85 and 113, respectively. Rams became azoospermic from day 29 to 71. The number of detectable spots per 2D gel decreased from 256 ± 31 to 104 ± 14 between days 0 and 29 (p < 0.05), returning to pre-insulation values on day 134. Several seminal proteins detected before insulation were absent when animals had low sperm motility or azoospermia, including albumin, arylsulfatase A, plasma glutamate carboxypeptidase, cathepsin F, transferrin, alpha-2-macroglobulin, angiotensin-converting enzyme, alpha fucosidase, beta galactosidase, TCP-1 containing chaperonins, heat shock protein 70 kDa, clusterin, palate, lung and nasal epithelium clone, ram seminal vesicle proteins, bodhesin 2, superoxide dismutase, cystatin B, peroxiredoxin 5, tissue inhibitor of metalloproteinase 2. Expression of other 17 proteins were quantitatively changed in the seminal plasma 2-D maps as the result of SI, such as actin, protein DJ-1, HRPE773-like, C-reactive protein precursor and porcine seminal plasma spermadhesins, among others. In conclusion, the expression of seminal plasma proteins was drastically altered by scrotal insulation, coincidental with changes in testis size and semen criteria. Proteins affected by heat stress are potentially involved in several events, from sperm protection and maturation to fertilization.